Motivational interviewing and interaction skills training for parents of young adults with recent-onset schizophrenia and co-occurring cannabis use: 15-month follow-up. Issue 13 (11th May 2015) - Smeerdijk, M.; Keet, R.; van Raaij, B.; Koeter, M.; Linszen, D.; de Haan, L.; Schippers, G.
Abstract : Background: There is a clear need for effective interventions to reduce cannabis use in patients with first-episode psychosis. This follow-up of a randomized trial examined whether an intervention for parents, based on motivational interviewing and interaction skills (Family Motivational Intervention, FMI), was more effective than routine family support (RFS) in reducing cannabis use in patients with recent-onset schizophrenia. Method: In a single-blind trial with 75 patients in treatment for recent-onset schizophrenia, 97 parents were randomly assigned to either FMI or RFS. Assessments were conducted at baseline and at 3 and 15 months after the interventions had been ended. Analyses were performed on an intention-to-treat basis using mixed-effect regression models. Results: From baseline to the 15-month follow-up, there was a significantly greater reduction in FMI compared to RFS in patients' quantity ( p = 0.01) and frequency ( p < 0.01) of cannabis use. Patients' craving for cannabis use was also significantly lower in FMI at 15 months follow-up ( p < 0.01). Both groups improved in parental distress and sense of burden; however, only FMI parents' appraisal of patients' symptoms showed further improvement at the 15-month follow-up ( p < 0.05). Conclusions: The results support the sustained effectiveness of FMI in reducing cannabis use in patients with recent-onset schizophrenia at 15 months follow-up. Findings were not consistent with regard to the long-term superiority of FMI over RFS in reducing parents' distress and sense of burden.